2017
DOI: 10.1245/s10434-016-5759-1
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Administration of Plasma-Activated Medium: Proposal of a Novel Treatment Option for Peritoneal Metastasis From Gastric Cancer

Abstract: Plasma-activated liquids may represent a novel therapeutic method for the treatment of peritoneal metastases in gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 32 publications
0
52
0
Order By: Relevance
“…Therefore, as a method that can extensively reach cancer cells in the peritoneal cavity, we have devised PAM and conducted basic research to utilize PAM for clinical use as an indirect plasma therapy. Interestingly, our colleagues and we have demonstrated the anti-tumor effects of PAM against several types of cancer using an in vivo model of peritoneal metastasis 8,11,19 . These findings suggest that PAM may be a novel option for the treatment of peritoneal metastasis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, as a method that can extensively reach cancer cells in the peritoneal cavity, we have devised PAM and conducted basic research to utilize PAM for clinical use as an indirect plasma therapy. Interestingly, our colleagues and we have demonstrated the anti-tumor effects of PAM against several types of cancer using an in vivo model of peritoneal metastasis 8,11,19 . These findings suggest that PAM may be a novel option for the treatment of peritoneal metastasis.…”
Section: Discussionmentioning
confidence: 96%
“…Previous reports revealed that longer treatments with direct exposure of NEAPP or PAM resulted in significantly lower viability in cancer cells 8,22 . In addition, Takeda et al revealed that not only adherent cells, but also floating cells, presented a decrease in adhesion capacity 19 . When applying PAM as part of a clinical treatment to prevent peritoneal metastasis, a shorter exposure time with PAM to the intraperitoneal cavity is necessary to minimize side effects on normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the ability of PAL to suppress ovarian cancer metastases when injected intraperitoneally in a mouse model was previously reported [24]. Yet, no evidence is available on the safety of PAL intraperitoneal administration in humans [41], supporting the need to shift the main focus of the plasma onco-medicine on liquids applicable to the clinical practice. This holds particularly true in OC, where spreading of the advanced stage disease within the pelvic cavity of the patient is often the case through the occurrence of micro-lesions [42], as washing the cavity with PA-RL may significantly reduce tumor burden, while sparing the non-cancer component.…”
Section: Discussionmentioning
confidence: 99%
“…In a xenograft mouse model, PAM inhibited the growth of ovarian and pancreatic cancer tumor cells [10,41]. Intraperitoneal injection of PAM/plasma-activated Ringer's lactate (PAL) inhibited the metastasis of ovarian, gastric, and pancreatic cancer tumors in disease model mouse experiments examining peritoneal metastasis [46][47][48]. However, in apoptosis induced by PAL, less ROS are produced in comparison with PAM [49], suggesting that components generated in PAM control the redox balance.…”
Section: Indirect Treatment: Pammentioning
confidence: 99%